ANALISIS KESALAHAN DALAM PENGGUNAAN SIMPLE FUTURE TENSE OLEH SISWA KELAS XI DI SMA NEGERI 9 MANADO - Pontoh, Garidhels S. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€Error Analysis in the Use of Simple Future Tense by Grade XI Sudents at SMA Negeri 9 Manadoâ€ is an attempt to identify and analyze the kinds of errors in the use of future tense by the students in Senior High School. This research is expected to give a contribution for teachers and students, in terms of developing a better English learning process in the use of future tense, particulary error analysis in the use of shall/will, be going to, be about to/be to, and present continuous as the future tenses mark. The method used in this research is descriptive method which has been done in several stages : preparation was made by reading the theory about simple future tense and the previous studies related to this research. Data was taken from 71 students in Binsus Science Class of SMA N 9 Manado,Â  by teaching and giving them test containing simple future tense material. Lennonâ€™s theory is used to explain how to analyze the use of future tense by grade XI student of SMA N 9 Manado. The result of this research shows that there are four kinds of errors in the use of simple future tense, these are addition, omission, substitution, and ordering errors. Errors of addition made by students are adittion be, infinitive to, about, will, s and â€“ed, -ing, have, be + -ing, and does + -ing. Errors of omission are pronoun, be, infinitive to,-ing, verb, going to, not, be + about to, about, about to + verb, be + not, going, and have. Errors of substitution are will, be, have, be + going to, be + to,be + -ing, -ing, open, and the. Errors of ordering are subjek and verb. Â  Key word: simple future tense and error analysis.